(3GdKbdGAs - (3GdeMhdj, CHh HcQ, GHf GdeQRHGf, eMnqeO Hf Nda Hf GdeQRHGf Hf HSGe, J (B309 (3g`s
(3ChdgG (B:s
(3MOKfG eMeO Hf Nda (B.. (3bGd CfTOfj GHf CHj GdOfjG hcJH Hg Edi GdeYJVO GejQ GdeDefjf hcGf jDOH GHf CejQ GdeDefjf Ydj GdecJaj (B...s
(3BNQgG (B:s
... (3aCbHdJ Ydi GdYLhR abGdJ CfG GdJj jbhd ajgG GdCYTi (B: (3de JeT ejdG hde JQBH Ydi bJH hde JQ GdTeS EdG OhfgG Gdcdd (B*** (3eG QhVI ef QjGV GdMRf eTHYI NVQGA LGO YdjgG eSHd gWd (B...(3bGdJ CfG gQjQI UGMHI GdCYTi , Jes
(3JHUQI GdYfhGf (B:s
(3QhGjI Ydj Hf eWgQ Hf egOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 \115s
(3EjVGM Gdecfhf (B1\543s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs